Halal Label and Purchasing Decisions in Fast Food Restaurants - Identiti, Identiti; Rimet, Rimet; Suryadi, Nanda; Museliza, Virna; Deli, Mazzlida Mat (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
This research explores the impact of halal certification on consumer purchasing decisions in Pekanbaru City's fast-food restaurants, emphasizing the significance of halal principles in a predominantly Muslim population. Using an explanatory research design with 30 participants, the study employs primary and secondary data sources, ensuring validity and reliability through robust measurement methods. Analyzing the results through simple linear regression, the research finds a substantial influence of halal certification on purchasing decisions, supported by a calculated t-value of 5.437. This indicates that clear halal certification significantly influences consumer choices, aligning with existing research on the importance of halal certification in the fast-food industry. Implications extend to fast-food operators in Pekanbaru, emphasizing the strategic value of obtaining and displaying halal certification. Clear certification enhances consumer trust and loyalty, providing a competitive edge in a market where halal considerations increasingly shape purchasing decisions. While the study acknowledges its focus on ready-to-eat food and considers potential external factors, future research could explore broader product categories and additional variables for a more comprehensive understanding of consumer behavior in relation to halal certification.